"My son was castrated as a result of a medical error. Is it OK to raise him as a eunuch?". (August 2021) - Johnson, Thomas W.; Wassersug, Richard J.
Abstract: A 12-year-old boy lost both testes after testicular torsion. He is now 14, and his father wants to know if the boy should immediately start supplemental testosterone or if he might reasonably choose to live as a eunuch. The boy does not yet express any strong opinion except that he is embarrassed about his weight gain. We advised the father that there is no need to rush the decision as the boy could at least delay testosterone therapy until his teens or early 20s and still go through male puberty with little risk of adverse health effects. We seek to know if others endorse our endocrinological advice. The boy's father wants to be honest with his son about the social challenges the boy may face if he elects to delay or avoid puberty altogether and chooses to openly identify as a eunuch. Highlights: A 12-year-old lost both testes following a misdiagnosed bilateral torsion. His father wants to know if he must take supplemental testosterone. His father wants to support him if he chooses to openly present as a eunuch.